2019
DOI: 10.1021/acscatal.9b00129
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Strength Neighboring Group Interactions Switch Polymerization to Dimerization Catalysis

Abstract: L, et al. (2019) Tailored strength neighboring group interactions switch polymerization to dimerization catalysis. ACS Catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The steric effect has been documented to play a vital role in ethylene dimerization catalyzed by Ni-based homogeneous catalysts. Hence, we evaluated this effect and found that the Ni center in Ni-ZIF-8 had a 51.7% buried volume within a 5 Å radius spherical space (Figure S19), which is similar to the values of the four-coordinated molecular Ni catalyst , and smaller than those of metal complexes with higher coordination numbers . Moreover, the two free ligands are loosely bonded to the Ni center and tend to leave during the reaction, providing sufficient space and vacant sites to facilitate ethylene adsorption and insertion.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The steric effect has been documented to play a vital role in ethylene dimerization catalyzed by Ni-based homogeneous catalysts. Hence, we evaluated this effect and found that the Ni center in Ni-ZIF-8 had a 51.7% buried volume within a 5 Å radius spherical space (Figure S19), which is similar to the values of the four-coordinated molecular Ni catalyst , and smaller than those of metal complexes with higher coordination numbers . Moreover, the two free ligands are loosely bonded to the Ni center and tend to leave during the reaction, providing sufficient space and vacant sites to facilitate ethylene adsorption and insertion.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this case, the Ni•••O intermediate appears to be rather stable and similar in energy to key species of catalysis (β-agostic and alkyl olefin complexes) but barely not yet an energetic sink that would impede catalysis. 47 In search for other suitable electron-withdrawing groups, we also explored pentafluorosulfanyl substituents. The SF 5 group (σ m = 0.61) has been well established in stoichiometric applications but curiously not in catalysis.…”
Section: Catalyst Development and Polymer Microstructurementioning
confidence: 99%
“…Cyclic voltammetry (CV) was employed as a further probe for the electron density of the metal site in the Ni–Me catalyst precursors. The obtained forward peak potentials of the Ni­(II)/Ni­(III) oxidation are indeed in the typical range for electron-rich , as well as electron-poor Ni­(II)/Ni­(III) pairs, whereas the corresponding salicylaldimines would show significantly higher oxidation potentials (Table ). For the nonprotonated complexes, half wave potentials of E = 27 mV ( 2 Me ) and E = 283 mV ( 2 CF3 ), respectively, were measured.…”
Section: Resultsmentioning
confidence: 69%